2016
DOI: 10.1684/ejd.2016.2833
|View full text |Cite
|
Sign up to set email alerts
|

Dermatological adverse events with taxane chemotherapy

Abstract: Taxanes (docetaxel and paclitaxel) are among the most commonly prescribed anticancer drugs approved for the treatment of metastatic or locally advanced breast, non-small cell lung, prostate, gastric, head and neck, and ovarian cancers, as well as in the adjuvant setting for operable node-positive breast cancers. Although the true incidence of dermatological adverse events (AEs) in patients receiving taxanes is not known, and has never been prospectively analysed, they clearly represent one of the major AEs ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
198
1
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 177 publications
(214 citation statements)
references
References 155 publications
8
198
1
7
Order By: Relevance
“…Other frequent skin toxicities included nail toxicity and hyperpigmentation, present in 76% and 79% of patients at inclusion respectively. These dAEs, which are very commonly observed after treatment with taxanes (Sibaud et al, 2016) have a negative impact on QoL, as demonstrated by an average baseline global DLQI score of 7.1 at inclusion in our total study population, which is comparable to that reported in patients with inherited ichthyosis (Bodemer et al, 2011), a skin disorder that has been described as having one of the most harmful impacts on QoL (Blanchet- Bardon, Corre, & Le, 2005).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Other frequent skin toxicities included nail toxicity and hyperpigmentation, present in 76% and 79% of patients at inclusion respectively. These dAEs, which are very commonly observed after treatment with taxanes (Sibaud et al, 2016) have a negative impact on QoL, as demonstrated by an average baseline global DLQI score of 7.1 at inclusion in our total study population, which is comparable to that reported in patients with inherited ichthyosis (Bodemer et al, 2011), a skin disorder that has been described as having one of the most harmful impacts on QoL (Blanchet- Bardon, Corre, & Le, 2005).…”
Section: Discussionsupporting
confidence: 79%
“…Dermatologic adverse events (dAEs) are commonly associated with breast cancer therapies, especially with taxanes (paclitaxel and docetaxel), usually prescribed as an (neo)adjuvant chemotherapy regimen. Taxanes may lead to skin rash, nail and hair changes, flushing, hypersensitivity reactions, hand-foot and PATEO syndromes, xerosis, pigmentary changes or pruritus in the majority of patients, depending on the dose and number of cycles (Robert et al, 2015;Sibaud et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these challenges and caveats, our data suggest that therapeutic cell cycle arrest approaches have the potential to prevent permanent taxane chemotherapy‐induced alopecia. Permanent chemotherapy‐induced alopecia following taxane treatment (Prevezas et al , ; Tallon et al , ; Miteva et al , ; Palamaras et al , ; Kluger et al , ; Tosti et al , ; Sibaud et al , ; Kang et al , ; Martín et al , ) is thought to arise in at‐risk individuals from irreversible stem/progenitor cell destruction and proliferative exhaustion (Paus et al , ). In this study, we show that proliferating (yet relatively slower cycling) anagen hair follicle outer root sheath keratinocytes situated within epithelial stem/progenitor cell niches (Purba et al , 2017b) are indeed susceptible to taxanes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the field currently lacks a model of how taxanes, major current oncotherapeutics used to treat breast and lung cancer, damage the human hair follicle and cause chemotherapy‐induced alopecia. The need for such a model is becoming increasingly important, given the abundance of reports describing permanent taxane chemotherapy‐induced alopecia (Prevezas et al , ; Tallon et al , ; Miteva et al , ; Palamaras et al , ; Kluger et al , ; Tosti et al , ; Sibaud et al , ; Kang et al , ; Martín et al , ). This is often reported following treatment with docetaxel, which is the subject matter of on‐going lawsuits against Taxotere (docetaxel) manufacturer Sanofi (Raymond, ).…”
Section: Introductionmentioning
confidence: 99%